Role of Seismic Refraction Tomography (SRT) in bedrock mapping; case study from industrial zone, Ain-Sokhna area, Egypt - EL HAMEEDY, Muhammad A.; MABROUK, Walid M.; DAHROUG, Said; YOUSSEF, Mohamed S.; METWALLY, Ahmed M. (Contributions to Geophysics and Geodesy, 2023)
In this study, eighteen compressional P-wave seismic refraction profiles survey was conducted on the western side of the Gulf of Suez, Egypt, to map bedrock topography, which is vital information in foundation pole placement and design for large factory construction. The configuration of the seismic survey consists of 10 metres geophone intervals (12 and 24 channels) with a total survey length of 3150 metres survey length. The seismic compressional wave velocity distribution reveals three layers ranging from (400 to 1100 m/s), (1200 to 2000 m/s), and (2200 to 3500 m/s). According to the data, the first low-velocity layer represents unconsolidated Wadi sediments. The second layer, on the other hand, comprises consolidated Wadi sediments, while the third layer comprises fractured to intact sandstone bedrock. The thickness of the first layer is believed to be between 0.5 and 10 m, while the thickness of the second layer is between 8.5 and 25 m. Pseudo-3D model of velocity distribution was constructed, revealing the presence of several low-velocity zones at a depth ranging from 15 to 32 m. Then, the topography of the non-rippable sandstone rock mass was mapped utilizing 3-D model. Finally, the correlation between seismic refraction tomography (SRT) results and nearby well logging dataset drilled by the Egyptian Geological Survey and Mining Authority (EGSMA) matched quite well. It may be inferred that, up to a depth of 15 to 32 metres, there is a high-velocity rock layer suitable for constructing deep foundations for multiple levels of the mega factory.